2010
DOI: 10.1002/ajim.20823
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to respirable dust and crystalline silica in bricklaying education at Dutch vocational training centers

Abstract: To assess a construction worker's lifetime exposure to respirable dust and crystalline silica, the vocational training period should also be taken into account. Several epidemiological studies have shown that time since first exposure can be an important risk factor for chronic health effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…40 The predominant past (and present) exposure for bricklayers is crystalline silica in the form of quartz dust, which concerns a substantial fraction (almost 20%) of the workforce in the construction industry 2 and occurs frequently during several tasks (concrete mixing, cutting, drilling, sandblasting, demolishing and cleaning). 41,42 Moreover, industrial hygiene assessments in several countries reported exposure concentrations of respirable crystalline silica for bricklayers above the exposure limit of 0.025 mg/m 3 (respirable quartz) [42][43][44][45][46][47][48][49][50][51][52][53] currently recommended by the American Conference of Governmental Industrial Hygienists (ACGIH). A quantitative job-exposure matrix developed for SYNERGY estimated for bricklayers exposures to respirable crystalline silica in 1998 ranging from 0.02 to 0.07 mg/m 3 .…”
Section: Literature Findingsmentioning
confidence: 99%
“…40 The predominant past (and present) exposure for bricklayers is crystalline silica in the form of quartz dust, which concerns a substantial fraction (almost 20%) of the workforce in the construction industry 2 and occurs frequently during several tasks (concrete mixing, cutting, drilling, sandblasting, demolishing and cleaning). 41,42 Moreover, industrial hygiene assessments in several countries reported exposure concentrations of respirable crystalline silica for bricklayers above the exposure limit of 0.025 mg/m 3 (respirable quartz) [42][43][44][45][46][47][48][49][50][51][52][53] currently recommended by the American Conference of Governmental Industrial Hygienists (ACGIH). A quantitative job-exposure matrix developed for SYNERGY estimated for bricklayers exposures to respirable crystalline silica in 1998 ranging from 0.02 to 0.07 mg/m 3 .…”
Section: Literature Findingsmentioning
confidence: 99%
“…A recent study on respirable dust exposure in bricklaying education institutions pointed however also towards sweeping as one of the major causes of high exposure levels. 22 When measuring a more specific exposure (e.g. quartz exposure), type of material appeared to be the strongest determinant of exposure.…”
Section: Discussionmentioning
confidence: 99%